2019
DOI: 10.2147/ott.s229033
|View full text |Cite
|
Sign up to set email alerts
|

<p>Serum Exosomal Long Noncoding RNA pcsk2-2:1 As A Potential Novel Diagnostic Biomarker For Gastric Cancer</p>

Abstract: Exosome-shuttled bioactive long non-coding RNA, as novel non-invasive biomarkers for cancer diagnosis, has received increasing attention. Here, we aimed to investigate the expression of serum exosomal long non-coding RNA pcsk2-2:1 (Exo-Lnc RNApcsk2-2:1) in patients of gastric cancer and evaluate its diagnostic value as a marker. Patients and methods: Exosomes were isolated from serum sample of gastric cancer using HiPure Exosomekits and identified via transmission electron microscopy, Western blotting, and nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 19 publications
3
30
0
Order By: Relevance
“…Recent observations have demonstrated that numerous lncRNAs are present in exosomes of cancers and show great potential as non-invasive tumor markers. 31…”
Section: Discussionmentioning
confidence: 99%
“…Recent observations have demonstrated that numerous lncRNAs are present in exosomes of cancers and show great potential as non-invasive tumor markers. 31…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies validated that exosomal lncRNAs can also serve as tumor biomarkers for GC. Chenchen suggested that the exosomal expression of LncRNA PCSK2-2:1 of GC patients was markedly downregulated compared to the control group, and was correlated with tumor size, stage, and venous invasion [ 102 ]. This study and researches alike validated the possibility to use lncRNAs to predict metastasis and prognosis of GC.…”
Section: Clinical Application Of Exosomal Rnas In Gcmentioning
confidence: 99%
“…12 For instance, the expression of serum exosomal lncRNA PCSK2-2:1 was significantly reduced in patients with GC, and downregulation of serum exosomal lncRNA PCSK2-2:1 was associated with adverse clinical parameters of GC. 13 Similarly, serum exosomal lnc-GNAQ-6:1 level was lower in GC patients and exhibited good performance for discriminating GC patients from healthy volunteers. 14 Myocardial infarction associated transcript (MIAT) was first identified as a lncRNA in 2006 and mapped to human chromosome 12q12.1.…”
mentioning
confidence: 94%
“…LncRNAs are found in circulating exosomes and might be used as candidate biomarkers for the detection and prognosis prediction of cancers 12 . For instance, the expression of serum exosomal lncRNA PCSK2‐2:1 was significantly reduced in patients with GC, and downregulation of serum exosomal lncRNA PCSK2‐2:1 was associated with adverse clinical parameters of GC 13 . Similarly, serum exosomal lnc‐GNAQ‐6:1 level was lower in GC patients and exhibited good performance for discriminating GC patients from healthy volunteers 14 …”
Section: Introductionmentioning
confidence: 99%